Comparative Gross Studies on Lungs of Aseel and Vanaraja Breeds of Poultry - Dewangan, B. K.; Ingole, S. P.; Chourasia, D. (Indian Journal of Veterinary Anatomy, 2013)
A comparative gross morphometric study of lungs was conducted in grower and adult poultry birds of Aseel and Vanaraja breeds. More body weight gain was noticed in Vanaraja (3322.14 gm) than Aseel (1472.43 gm) in both the groups which may be attributed to its germplasm. The percentage contribution of the lungs to the body weight and weight specific volume of lungs were highly significant in Aseel to that of Vanaraja. In both the groups, the length of left lung was 0.03-0.18 cm more than right lung. While, the thickness of left lung was 0.02-0.06 cm less than right lung in both the groups.